The music of Vigo’s "movida" and the Russian "rock-poetry" of the same time period - Sokolova, María (Madrygal. Revista de Estudios Gallegos, 2013)
This article tries to reflect similarities and differences in the cultural processes of Spain and Russia/USSR in the eighties of the last century, particularly in relation to what is known as movida. It is analyzed the similarities in the names of musical groups, titles and lyrics, music, performance characteristics, the attitude of the musicians in relation to their work and the social and political environment.
Keywords: movida; eighties; music; Vigo; Russia/USSR